Test Of Nominal Prices Of Sukuk In Indonesia - et. al., Dudi Abdul Hadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The nominal price of the sukuk has become an important element for companies and investors in determining the real value of the company from the perspective of companies and investors. The company determines the type of contract, maturity, maturity based on the type of contract and size of the company as an important element in determining the nominal price of sukuk according to research in 2016. A mathematical model has been formulated in the form of a multiple linear regression equation. This model has not been tested for reliability so that testing and research is needed in another year. 2019 is a comparative year for conducting research. The research was carried out in an exploratory manner. The sample used was 134 sukuk circulating in Indonesia. The result of the research shows that the nominal price of the sukuk predicted by the old model is correlated with the nominal price of the current sukuk at the 5% significance level.